Representações sociais da África e dos negros africanos em livros didáticos de geografia do ensino fundamental II: PNLD 2014 e 2020 - Oliveira, Ana Flávia Borges de (2023)
The present research aims to analyze and discuss the images that represent Africa and black Africans in Geography Textbooks for the Final Years of Elementary School in two editions of a selected collection that was approved by the National Program of Books and Teaching Materials in 2014 and 2020. Textbooks are understood as carriers of an ideological value system, which convey ideas, cultures and representations and, therefore, become an important object to verify the images of black Africans and Africa, positioning this research in favor of the struggle for an anti-racist Geography Teaching. Law 10639, enacted in January 2003, is seen as the main tool in the fight against racism in the field of education, impacting, for example, the production of didactic materials in the most varied fields. This is because it has as a premise the valorization of Afro-Brazilian and African history and culture, and the education of ethno-racial relations. The textbook is still today one of the most used educational materials by teachers, especially in public schools, and in most of these materials there is still the presence of forms of discrimination against black Africans and distorted images of Africa, in addition to the presence of stereotypes, which are equivalent to a kind of label used to conveniently qualify ethnic-racial groups. The research methodology makes use of a bibliographical survey, having as main referential the Theory of Social Representations, by the romanian social psychologist Serge Moscovici (2003) and of Controlling Images, the american sociologist and black feminist Patricia Hill Collins (2019), and black and non-black researchers who contribute to Black Geography. The results obtained point to discrepancies in the representation of the black population in relation to the white one, still reproducing a colonial and Eurocentric discourse. In most images black Africans are represented in inferior positions of less prestige and in subordinate conditions; and the continent of Africa is portrayed as primitive, wild and poor.